Kajian Tentang Pendidikan dan Pelatihan Terhadap Kinerja Serta Dampaknya Kepada Promosi Jabatan - Fajar Apit Firmanto (Program Pascasarjana Universitas Gajayana, 2019)
Education and training is one of the important factors in placement, especially for all Alumi/former Poltekad graduates, because the implementation of education and training will make the performance of alumi/former Bintara Poltekad graduate students increase or better than before conducting education or training in Poltekad. The results of this study indicate that: i) Education has a significant influence on the performance of the former Diploma 3 Student Class Batch of XXIV Polytechnic; ii) Training has a significant influence on the performance of former Diploma 3 Students in Class XXIV Poltekad; iii) Performance has a significant effect on the promotion of positions of former Diploma 3 Students in Class XXIV Poltekad; iv) Education has a significant influence on job promotion from former Diploma 3 Students in Class XXIV Poltekad; v) Training has a significant influence on job promotion from former Diploma 3 Students in Class XXIV Poltekad; vi) Education has a significant influence on job promotion through the performance of former Diploma 3 Students in Class XXIV Poltekad; vii) Training has a significant influence on job promotion through the performance of former Diploma 3 Students in Class XXIV Poltekad.